2006
DOI: 10.1080/13691050600665048
|View full text |Cite
|
Sign up to set email alerts
|

Gender dynamics in the primary sexual relationships of young rural South African women and men

Abstract: A substantial body of South African research describes the importance of gender dynamics within sexual relationships as factors underlying HIV risk, yet we know little about these factors among young adults-a group at exceptionally high risk of infection. Our primary objective was to explore the ways that young adult men and women interpret and enact gender roles within their established primary partnerships, and how these dynamics influence sexual behaviour in relation to HIV risk. We employed script theory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 33 publications
4
53
1
Order By: Relevance
“…These findings support our earlier qualitative research, which suggested that both men's and women's ideas of normative gender roles in sexual relationships are changing but that enactment of new roles is a slow and dynamic process. 27 In the current study, young women's endorsement of egalitarian gender roles in sexual relationships appears to impact positively on levels of condom use. However, gender role norms related to partnering practices and heterosexual relationships are still governed by dominant masculinities and prevailing patriarchal norms.…”
Section: Gender Role and Relationship Norms Among Young South Africanmentioning
confidence: 92%
See 3 more Smart Citations
“…These findings support our earlier qualitative research, which suggested that both men's and women's ideas of normative gender roles in sexual relationships are changing but that enactment of new roles is a slow and dynamic process. 27 In the current study, young women's endorsement of egalitarian gender roles in sexual relationships appears to impact positively on levels of condom use. However, gender role norms related to partnering practices and heterosexual relationships are still governed by dominant masculinities and prevailing patriarchal norms.…”
Section: Gender Role and Relationship Norms Among Young South Africanmentioning
confidence: 92%
“…11,27 Script theory posits that normative beliefs about gender roles guide heterosexual interactions at the individual, interpersonal and cultural levels. [30][31][32] We hypothesized that higher endorsement of violence, power and male dominance would be negatively correlated with safer sexual behaviors, measured here as condom use and fewer sexual partners, among both men and women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The province of KwaZulu-Natal, where this research was conducted, has experienced some of the highest levels of infection in the country, with one-third of pregnant women now infected (Department of Health 2005). Young women's vulnerability to HIV/AIDS is increased by gender violence, rape and the gendered nature of their roles within heterosexual relationships (O'Sullivan et al 2006). The current context in post-apartheid South Africa has seen rising unemployment and social inequalities, which has exacerbated HIV prevalence rates, especially amongst black men and women.…”
Section: Introductionmentioning
confidence: 99%